2003
DOI: 10.1515/bc.2003.095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Human Cathepsin B: Implication in Pathologies

Abstract: Cathepsin B is a papain-family cysteine protease that is normally located in lysosomes, where it is involved in the turnover of proteins and plays various roles in maintaining the normal metabolism of cells. This protease has been implicated in pathological conditions, e.g., tumor progression and arthritis. In disease conditions, increases in the expression of cathepsin B occur at both the gene and protein levels. At the gene level, the altered expression results from gene amplification, elevated transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 62 publications
3
79
0
2
Order By: Relevance
“…6A). The HDI-alb Ø induced cathepsin B protein differed in size from the lysosomally-processed fully mature form 37 found in control cultures (Fig. 6A), supporting the gene expression and cytology data (above) suggestive of altered lysosomal activity.…”
Section: Isocyanate-albumin Induced Changes In Cellular Proteinssupporting
confidence: 82%
“…6A). The HDI-alb Ø induced cathepsin B protein differed in size from the lysosomally-processed fully mature form 37 found in control cultures (Fig. 6A), supporting the gene expression and cytology data (above) suggestive of altered lysosomal activity.…”
Section: Isocyanate-albumin Induced Changes In Cellular Proteinssupporting
confidence: 82%
“…Numerous studies have shown that Ctsb and other cathepsins can function in degrading the extracellular matrix (ECM) in association with multiple processes, including endothelial tube formation (Cavallo-Medved et al, 2009), tumor cell progression (Bengsch et al, 2013;Buck et al, 1992;Koblinski et al, 2002;Porter et al, 2013;Turk et al, 2000;Yan and Sloane, 2003) and rheumatoid arthritis (Hashimoto et al, 2001). The ECM components fibronectin and laminin are first evident at 65% epiboly in zebrafish embryos (Latimer and Jessen, 2010), which is a stage after we first observed defects in split top mutants, suggesting that ECM degradation is not an essential maternal function of Ctsba.…”
Section: Discussion Ctsba Endopeptidase Function In Developmentmentioning
confidence: 82%
“…This class of proteases is capable of degrading extracellular matrix components (20)(21)(22); thus, cysteine proteases have long been considered of potential importance during tumor cell invasion and metastasis (55,56). Cystatin M is a secreted protein and, when expressed at appropriate levels, functions to constrain extracellular cysteine protease activity (27).…”
Section: Discussionmentioning
confidence: 99%